The dynamics of diagnosis of salivary gland tumours: histopathology matters - Venugopal, Madabhushi; Devi, Chaganti Padmavathi; Deepthi, Kuppili; Mutte, Koteswari (International Journal of Research in Medical Sciences, 2017)
Background: Tumours of salivary glands are rare neoplasms of head and neck region accounting for less than one percent of all tumours. Parotid gland accounts for majority of tumors followed by submandibular gland. As such many challenges are encountered in establishing histological diagnosis, classification, grading and management of salivary gland neoplasms. This study is taken up to study the incidence of salivary gland tumours in our institution and analyse histological criteria for diagnosis and grading systems in vogue for common malignant lesions. Methods: Clinical data at presentation, resected specimens received from Government General Hospital, Guntur and tissue sections stained with Haematoxylin & Eosin are retrieved from the archives in the Department of Pathology for the study. Relevant Immunohistochemical markers are done in difficult cases. Salivary gland tumours reported between 2011 and 2015 in the Department of Pathology, Guntur Medical College, Guntur, are taken for the study. Results: Majority of the salivary gland tumours in our study were observed in the fourth and fifth decades with a male preponderance (62.68%). Parotid gland was the most common site (83.63%) for all tumours and pleomorphic adenoma was the most common tumour with 76 out of 110 cases (69.09%). Other benign tumours in the study included three cases each of Warthin tumour and basal cell adenoma. Malignant tumours accounted for 28 out of 110 tumours (25.45%). Mucoepidermoid carcinoma (MEC) was the most common malignant lesion in the study with 13 cases (46.42%). Conclusions: Salivary gland tumours are rare. But the wide spectrum of tumour entities and histological complexities lead to diagnostic problems in many cases. Pleomorphic adenoma was the most common tumour overall and parotid gland was the most common site for both benign and malignant tumours.